METODE IMLA' DALAM UPAYA MENINGKATKAN KETERAMPILAN MENULIS HURUF ARAB - Solchan Ghozali (MIYAH : Jurnal Studi Islam, 2019)
Abstract: This article aims to discuss the learning process of writing words in Arabic with the existence of imla' learning techniques and knowing the improvement in learning outcomes menulis Arabic words for students of class IIB MINU Kedungrejo. By using quantitative descriptive research types, especially quantitative experiments. While the research design is in the form of One-Group Pretest-p osttestdesigns. The data collec-tion techniquesused are tests and documentation. The data analysis technique used is quantitative analysis. The results obtained by comparing between the magnitude of t obtained in the calculations listed on the value of t count m can be seen that t count is smaller than - t table, where t count = -5.71 while t table = 2.093. Based on such calculations, t count is smaller than - t table, where t count = -5.71 < - 2.093 = - t table. Thus reject Ho. Reject Ho means Imla' learning is effective in improving the skills of writing Arabic letters. Keywords: Imla' Learning, Ability to Write Arabic Letters.